PENGARUH TINGKAT PENDIDIKAN MANAJER TERHADAP KINERJA PERUSAHAAN GO-PUBLIC - ., Moerdiyanto (Jurnal Cakrawala Pendidikan, 2015)
Abstract: The Effect of Managers' Educational Levels on the Go-PublicCompany Performance. This study aims to investigate the effect of managers'educational levels on the company performance. The population comprised allthe manufacturing companies listed in the Indonesian Capital Market duringthe period of 2003-2007. The sample, consisting of 60 companies, was selectedusing the purposive sampling technique. The variable of managers' educationallevels was controlled by the variables of accounting income and cash flows. Thedata on managers' educational levels were collected through a questionnaireand those on accounting income and the cash flows through documents fromthe company financial statement published in the Indonesian Capital Market.The data on the stock returns movement as a company's performanceparameter were obtained from the Indonesian Securities Market Database(ISMD). The data were analyzed using the data panel regression, employing thesoftware of EVIEWS-3 program. The result shows that the regression coefficientof managers' educational levels on the company performance is positive andstatistically significant with Î± 1% and t-value at p < 0.01. Keywords: managers' educational levels, accounting income, cash flow, go- public company performance